Does Danish football club Brøndby swim with the fishes? An application of the reversed news model - Carsten Croonenbroeck; Fabrizio Leonardo Monaco; Mads Julius Christensen (European University Viadrina, Department of Business Administration and Economics, 2012)
We complement a former study by Jørgensen, Moritzen and Stadtmann (2012) and estimate a reversed news model for the Danish publicly listed football club Brøndby. In addition to match outcome (as in Jørgensen et al.), news related to corporate governance and the financial status are also important.
Keywords: G14; L83; G32; 330; Reversed News Model; Asset Prices; Stock Market